Vocational Certainty and Career Factors in Students of two Northwestern Universities of Mexico - González Lomelí, Daniel (Consorcio de Universidades Mexicanas A.C., 2018)
Choosing a career is a fundamental decision-making process with implications for the future development of adolescents. Adolescents are immersed in a continually transforming world where skill development is continuous. The main objective of this study was to explore a causal model of vocational certainty (CV) predicted by cognitive and emotional career factors (FC) in students from two different institutions in northwestern Mexico. Further, CV and FC profiles of each sample were compared. Sociodemographic variables (such as gender, type of career option, employment status, having completed courses or subjects of vocational guidance during high school, university and career in which he studies) were also included in the model. Based on structural equation modeling (n= 248 higher education students), results showed that career factors were informed by career information and anxiety. In turn, career choice explained 55% of vocational certainty variability. Additionally, differences were found between the vocational profiles in students from the two different universities. These results contribute evidence highlighting the importance of measuring relevant variables in the study of career decision making.